Proton observed phosphorus editing (POPE) for in vivo detection of phospholipid metabolites. (25th November 2015) - Wijnen, Jannie P.; Klomp, Dennis W. J.; Nabuurs, Christine I. H. C.; de Graaf, Robin A.; van Kalleveen, Irene M. L.; van der Kemp, Wybe J. M.; Luijten, Peter R.; Kruit, Mark C.; Webb, Andrew; Kan, Hermien E.; Boer, Vincent O.
Abstract : The purpose of this article was to compare the sensitivity of proton observed phosphorus editing (POPE) with direct 31 P MRS with Ernst angle excitation for 1 H– 31 P coupled metabolites at 7 T. POPE sequences were developed for detecting phosphocholine (PC), phosphoethanolamine (PE), glycerophosphocholine (GPC), and glycerophosphoethanolamine (GPE) on the 1 H channel, thereby using the enhanced sensitivity of the 1 H nuclei over 31 P detection. Five healthy volunteers were examined with POPE and 31 P‐MRS. POPE editing showed a more than doubled sensitivity in an ideal phantom experiment as compared with direct 31 P MRS with Ernst angle excitation. In vivo, despite increased relaxation losses, significant gains in signal‐to‐noise ratio (SNR) of 30–40% were shown for PE and GPE + PC levels in the human brain. The SNR of GPC was lower in the POPE measurement compared with the 31 P‐MRS measurement. Furthermore, selective narrowband editing on the 31 P channel showed the ability to separate the overlapping GPE and PE signals in the 1 H spectrum. POPE can be used for enhanced detection of 1 H– 31 P coupled metabolites in vivo . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We demonstrate the enhanced sensitivity of proton observed phosphorus editing (POPE) over direct 31 P MRS with Ernst angle excitation for 1 H– 31 P coupled metabolites in the human brain at 7 T.